Fine-needle aspiration to improve diagnosis of melioidosis of the head and neck in children: a study from Sarawak, Malaysia - Mohan, Anand; Podin, Yuwana; Liew, Da-Wei; Kumar, Jeevithaa Mahendra; Lau, Peter Sie Teck; Tan, Yee-Yen; Tai, Yi-Pinn; Gill, Ranveer Singh; Shanmugam, Ram; Chien, Su Lin; Tan, Lee See; Mat Sani, Nurul Asiah; et al. (Springer Nature, 2021)
Melioidosis, the infection caused by Burkholderia pseudomallei, is associated with a high case fatality rate, due in part to difficulties in clinical recognition and diagnostic confirmation of the disease. Although head and neck involvement is common in children, specific disease manifestations differ between geographic regions. The aim of this study was to provide a detailed description of melioidosis of the head and neck among children in Sarawak, Malaysia, and determine if fine-needle aspiration of suspected head or neck lesions could improve melioidosis diagnosis.